2006
DOI: 10.1080/03639040600832827
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Molecular Dispersion in Microparticles of Ammonio Methacrylate Copolymer and Ethylcellulose Binary Blends for Controlled Drug Delivery: Effect of Matrix Composition

Abstract: The objective of this study is to explore matrix-type microparticles, comprising a solid dispersion of drug with an ammonio methacrylate copolymer and ethylcellulose binary blend, for use in the controlled release of a poorly water-soluble drug, nifedipine. Microparticles consisting of an ethylcellulose N7 (N7) and Eudragit RL (RL) binary blend at different ratios were prepared using phase-separation methodology. The effects of matrix composition on microparticle properties were evaluated by polarized light mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…Doses of only two to three times the therapeutic dose may cause profound toxicity and side effects in susceptible individuals. Therefore, it is desirable to develop nifedipine controlled-release dosage forms to reduce the side effects, to prevent toxicity, to extend a half-time and to improve patient compliance (Buckley et al, 2007;Huang, Wigent, & Schwartz, 2006). Recently, nifedipine has been used in such controlled-release studies as alginate-methyl cellulose blend microspheres, chitosan-graft-acrylamide microspheres, alginate-chitosan hydrogel beads (Babu et al, 2007;Dai, Li, Zhang, Wang, & Wei, 2008;.…”
Section: Introductionmentioning
confidence: 98%
“…Doses of only two to three times the therapeutic dose may cause profound toxicity and side effects in susceptible individuals. Therefore, it is desirable to develop nifedipine controlled-release dosage forms to reduce the side effects, to prevent toxicity, to extend a half-time and to improve patient compliance (Buckley et al, 2007;Huang, Wigent, & Schwartz, 2006). Recently, nifedipine has been used in such controlled-release studies as alginate-methyl cellulose blend microspheres, chitosan-graft-acrylamide microspheres, alginate-chitosan hydrogel beads (Babu et al, 2007;Dai, Li, Zhang, Wang, & Wei, 2008;.…”
Section: Introductionmentioning
confidence: 98%
“…Due to which we can administer adequate amount of drug for an extended period of time, which in turn offer many benefits such as reduced dosing frequency leading to patient compliance, decreased side effects, prolonged therapeutic effect for poorly water-soluble and short biological half-life drugs. The polymers which are used include ethyl cellulose, hydroxypropyl cellulose, Eudragit RS, RL, poly (ethylene oxide) and carboxyvinyl polymer [25,26] .…”
Section: Fourth Generation Solid Dispersionmentioning
confidence: 99%
“…EC polymers are widely known to be pH independent and water-insoluble materials. Recent evidence has suggested that the combination of EC and methacrylic polymers at different ratios is able to control drug release (Sanchez-Lafuente et al, 2002;Huang et al, 2006;Feng et al, 2008). Based on these reports, the authors speculated that the incorporation of EC into a wax matrix containing AMCE would control the release of APAP as desired, but little information is available regarding wax matrices composed of a combination of EC and AMCE.…”
Section: Introductionmentioning
confidence: 96%